Autoria e colaboração criativa no projeto arquitetônico - Paulo Waisberg (2007)
This work is about the changes in the architectural practice caused by the transformation on authorship and the development of new information technologies. Other factors such as spatial and temporal concentration and its effects on collaboration are used as material for a comparative study between two types of architectural design studios at the architecture school of Universidade Federal de Minas Gerais, Brazil. In the first type, the participation as a professor on a Virtual Design Studio is described. This is an ongoing project and constitutes an interactive environment fordesign collaboration using computer mediated communication among Brazilian universities. The Virtual Design Studios are Studios distributed in space and time, in which participants are located at different places and use synchronous and asynchronous communication. In the second type, a subject on architectural competition design studio was created, having the same amount of class-hours of the former but concentrated on a week and having the participants share the same laboratory.Conclusions from these experiments are used as bases for a contribution on the understanding of the variables that affect the team creative collaboration.